Testable code detection tool for object oriented programming. A tool for novice programmer - Hisamudin, Saiful Bahri (2019)
Automated software testing has gained huge attention in the last past decades due to the rapid software development cycles. Ever increasing inherent complexity, dynamic behaviors in system as well as new development paradigm required tedious work in software testing. Object oriented design and programming has become the dominant development paradigm for software projects and widely used in software development industry. The concept of object oriented ease the software development process but it make the testing process difficult. Subsequently, this will increase the testability effort in software program. Prior researches analyze the complexity and testability using object oriented design metrics where these research notably state that different attributes may add directly to the complexity of design that require more testing efforts. This research will focus on detecting the non-deterministic characteristics in software program. A tool developed which able to detect pattern in method in object oriented programming to determine the testability of the software product. The testing tool is aim at to guide novice programmer to write testable code during software development process.